Oncologic safety of the submental flap for reconstruction in oral cavity malignancies - Howard, Brittany E; Nagel, Thomas H; Donald, Carrlene B; Hinni, Michael L; Hayden, Richard E (Otolaryngology-head and neck surgery, 2014)
To evaluate the oncologic safety of the submental flap regarding potential transposition of involved nodes to the reconstruction site and recognize the submental flap as an excellent option for oral cavity reconstruction. Case series with chart review. Tertiary academic referral center. All patients undergoing reconstruction with submental flaps following the resection of primary and recurrent malignancies of the oral cavity between 2002 and 2012 were reviewed. Analysis included tumor location, staging, reconstructive details, postoperative course, and outcomes. Fifty patients were identified having undergone submental flap reconstruction of defects following resection for oral cavity malignancies. No patient had identifiable clinical or radiographic level I nodal involvement preoperatively. Patients' ages ranged from 35 to 88 years (mean, 70 years). American Joint Committee on Cancer staging of patients included stage II (n = 16, 32%), stage III (n = 10, 20%), and stage IVa disease (n = 28, 48%). All patients underwent a level 1A and 1B dissection with removal of the nodal basin and submandibular gland. The prevalence of occult lymph node metastasis involving level 1 was 10%. On follow-up, there were no local recurrences associated with submental flap transposition to the oral cavity. One patient with multifocal oral disease had a tongue recurrence geographically separate from the submental flap reconstruction. There was 100% flap survival. The submental flap provides a rapid and reliable option for oral cavity defect reconstruction. With appropriate management of the level 1 nodal compartment, oncologic outcomes are not compromised.